Why and How There Should be More Europe in Development Policy - Christoph Harendt; Friedrich Heinemann; Stefani Weiss (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Extreme poverty in certain global regions remains one of our greatest international challenges. Between 2014 and 2016, 800 million people suffered from hunger. Nevertheless, most EU member states spend less than the required 0.7 percent of Gross National Income (GNI) for development aid. In addition, resource use is often inefficient since multiple donors often engage in the same countries, which incurs high administrative and transaction costs for both donors and partners. Using the concepts of fiscal federalism, we argue that shifting more financing and management of development cooperation from member states to the EU would contribute to overcoming these problems. A larger role of the EU budget for financing development aid would better align national costs and benefits and thus reduce free riding. Moreover, transaction costs could fall by reducing aid fractionalization. Based on the general insight that stronger EU competence would be favourable, we have developed a model of how this could work. In this model, the centralised development aid from the EU budget would meet the 0.7 percent spending commitment. Since member states contribute to the budget according to their GNI, this target could be met by the EU as a whole as well as the member states. If large income differentials between member states render this GNI-proportionate financing formula unacceptable, a progressive formula could be applied for the development-related contributions to the EU budget. However, member states with equal income levels would be treated equally, thus precluding free riding. The model accounts for the main challenge that a further centralisation of European development aid would face: the need to account for specific national interests in development aid that result from historical links, national interests, and citizens' preferences. As well as the EU budget component, individual member states could conduct additional development financing via trust funds, which would also enable them to pursue individual preferences. On the operational side, we propose a system in which member states remain involved by being responsible as 'lead states' (or part of a small group of lead states) for the implementation of development cooperation with one or several partner countries. The lead states would act on behalf of the EU and administer aid in a specific partner country. This kind of specialization could overcome the current inefficient aid fragmentation without losing the expertise and information advantages from long-standing ties between donors and recipients.
Keywords: 330